MENINGKATKAN HASIL BELAJAR SISWA KELAS IV UPT SPF SD INPRES MACCINI I/1 PADA MATA PELAJARAN PPKN DENGAN MENGGUNAKAN APLIKASI QUIZIZZ: Penelitian Tindakan Kelas - Sahrina Said; Tri Putri Paurru; Randy Saputra Mahmud; Wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve the learning outcomes of class IV UPT SPF SD Inpres Maccini I/1 students in Civics subjects by using the Quizizz application. This type of research is classroom action research. The research subjects were 34 students in class IV B at UPT SPF SD Inpres Maccini I/1. The data collection method in this research uses tests and observation. The research instrument is a quiz question test in the Quizizz application and direct observation in the learning process. The indicators for the success of actions for learning outcomes are marked by ≥70% of the total number of students who take part in the learning process having obtained a score of ≥70. The research results show an increase in student learning outcomes after using the Quizizz learning media. The average learning outcome was 65 in cycle I then became 75 in cycle II. The percentage of students who obtained a score ≥70 increased, namely 44% in cycle I and to 73% in cycle II.